Self-assessment of the singing voice. State of the art and required investigations - Capucho, Clara (2011)
The purpose of this paper is to review the medical literature in the topic of the self-assessment of singing voice, describe the instruments that have been used for this purpose, describe the process of their creation and validation and point out topics of research needed in this area in Portugal.Traditionally, the evaluation of the disease or the assessments of the treatment outcomes were based in clinical observation and exams like laryngoscopy. Only recently the impact of disease in the quality-of-life of the patients, from their own perspective, was considered. Self-reported questionnaires include assessment of multidimensional aspects of the disease like impairment, disability and handicap. These instruments are very robust statistically, making them interesting for clinical purposes and for being used universally in investigation.More than ten self-reported questionnaires were created for the speaking voice, but the Voice Handicap Index (VHI), created in 1997, and consisting of 30 items divided into three different subscales: physical, functional and emotional, has shown to be superior to other instruments. VHI is adequate to the study of a greater variety of vocal pathologies and is superior in determining the modification in voice complains that results from treatments. The VHI has also become more popular, being already translated into 14 languages, including portuguese from Portugal.The first instrument designed specifically for self-evaluation of singing voice was created in Belgium in 2005 but it was in the U.S., in 2007, that other instrument was created that is considered the reference in this area - the Singing Voice Handicap Index (SVHI). The SVHI proved that there are factors specific to the singing voice that can be identified and the instrument is more sensitive than the VHI to detect changes in voice and to evaluate the efficacy of the treatments. It would be interesting to translate and validate the instrument into Portuguese from Portugal, to offer this instrument to the otolaryngologists who treat singers and want an objective assessment of the impact of disease and treatment outcomes in these patients. The process of translation and validation for Portuguese SVHI has started in the Voice Clinics of the Hospital de Egas Moniz, and is now nearing completion.